Role of the intercalated disc in cardiac propagation and arrhythmogenesis - Kleber, Andre G.; Saffitz, Jeffrey E. (Frontiers in Physiology, 2014)
Abstract This review article discusses mechanisms underlying impulse propagation in cardiac muscle with specific emphasis on the role of the cardiac cell-to-cell junction, called the “intercalated disc”. The first part of this review deals with the role of gap junction channels, formed by connexin proteins, as a determinant of impulse propagation. It is shown that, depending on the underlying structure of the cellular network, decreasing the conductance of gap junction channels (so-called “electrical uncoupling”) may either only slow, or additionally stabilize propagation and reverse unidirectional propagation block to bidirectional propagation. This is because the safety factor for propagation increases with decreasing intercellular electrical conductance. The role of heterogeneous connexin expression, which may be present in disease states, is also discussed. The hypothesis that so-called ephaptic impulse transmission plays a role in heart and can substitute for electrical coupling has been revived recently. Whereas ephaptic transmission can be demonstrated in theoretical simulations, direct experimental evidence has not yet been presented. The second part of this review deals with the interaction of three protein complexes at the intercalated disc: (1) desmosomal and adherers junction proteins, (2) ion channel proteins, and (3) gap junction channels consisting of connexins. Recent work has revealed multiple interactions between these three protein complexes which occur, at least in part, at the level of protein trafficking. Such interactions are likely to play an important role in the pathogenesis of arrhythmogenic cardiomyopathy, and may reveal new therapeutic concepts and targets.